The prevalence of constipation in end-stage kidney disease patients: A cross-sectional observation study. Issue 43 (28th October 2022) - Zhang, Liuping; Tang, Fang; Wang, Fengmei; Xie, Qinglei; Xia, Meixia; Jiang, Liangyunzi; Wang, Ze-Mu; Wang, Bin
Abstract : The aim of our study was to determine the prevalence, distribution, and risk factors for constipation in peritoneal dialysis (PD) and hemodialysis (HD) patients in our center. In this cross-sectional study, 858 dialysis patients over 18 years of age (681 HD cases and 177 PD cases from our hospital) were enrolled. A constipation assessment scale (CAS) questionnaire was used to evaluate constipation status. Logistic regression analysis was performed to define independent risk factors for CAS scores. The prevalence of constipation in HD and PD patients was 52.7% and 77.4%, respectively. The mean CAS score in HD and PD patients was 1.73 ± 2.31 and 2.42 ± 2.34, respectively. Age ≥ 65 and diabetic kidney disease for renal failure were independent risk factors associated with constipation in the HD population (OR = 1.67, 95% CI: 1.15–2.90, P = .019; OR = 3.31, 95% CI: 1.65–6.11, P < .001, respectively). In the PD population, only serum prealbumin was independently associated with constipation (OR = 0.88, 95% CI: 0.79–0.96, P = .007). The multivariable logistic regression analysis demonstrated that PD modality, age ≥ 65 and diabetic kidney disease for renal failure were independent risk factors for constipation (OR = 2.15, 95% CI: 1.41–3.32, P < .001; OR = 1.65, 95% CI: 1.13–2.33, P = .003; OR = 3.19, 95% CI: 1.76–5.093, P < .001, respectively). The prevalence of constipation in PD patients was higher than that in HD patients in our center. PD modality for renal replacement therapy, age ≥ 65 and diabetic kidney disease for renal failure were closely associated with constipation in dialysis patients.